Preparation of water-based hydrophobic coatings by silica-based composite for natural and synthetic fabrics - Nurul Hidayah, Abu Bakar (2024)
Hydrophobic coatings, inspired by the lotus effect, have gained popularity due to their ability to solve various problems in diverse industries. Traditional methods, reliant on harmful organic solvents and fluorinated chemicals face environmental concerns, necessitating the adoption of water-based coatings. However, challenges persist in synthesizing stable low surface energy (LSE) materials in water and finding suitable adhesives for fabric coatings. Thus, this study aims to synthesize modified silica-based hydrophobic coatings using a water-based sol-gel method by optimising precursor ratios and curing temperatures, confirm low surface energy properties via the modified Zisman plot, and investigate the coated fabrics durability and stability. The coating solutions were synthesized by cross-linking the first precursors, tetraethyl orthosilicate (TEOS) and hexyltrimethoxysilane (HTMS) with their second precursors, polydimethylsiloxane (PDMS) and hexyltriethoxysilane (HTES), respectively. Then, the coatings were coated onto the cotton and polyester fabrics using pad-dry-cure method. These two coatings were compared in terms of their cost-effectiveness and hydrophobicity. The highest water contact angle (WCA) for both cotton and polyester fabrics was achieved at a molar ratio of 1:0.25 TEOS:PDMS and 1:0.6 HTMS:HTES, indicating excellent hydrophobicity. Only TEOS-PDMS coating was then chosen for in-depth studies and characterizations due to its lower cost and the WCA value difference between the coatings is only 2.89%. Effect on curing temperature, swelling test, LSE calculation and further characterizations, including elemental composition, morphology, breathability, strength, washing and durability, was conducted for the coating. The coated polyester and cotton fabrics managed to achieve WCA as high as 136.59° and 133.06° respectively, at curing temperature of 120 °C. The slight swelling of the TEOS-PDMS polymer gel in water and larger swell in other solvents suggest the successful formation of non-polar hydrophobic gel. FTIR analysis confirmed the formation of Si-O-Si bonds in the coating solution, while SEM-EDX analysis revealed successful adhesion and surface roughness of the coating to the fabric surfaces, particularly on cotton. Surface energy of the coated cotton and polyester were determined at 37.4 mN/m and 39.1 mN/m respectively, through the modified Zisman plot. The coated fabrics exhibited a remarkable increase in thermal stability and retained hydrophobicity at high temperatures. However, there were reductions in air permeability as much as 96.63% for cotton and 55.43% for polyester. Similarly, the strength of the coated fabrics decreased, with breaking strength reductions of up to 30.62% and 24.90% for both cotton and polyester, and tearing strength reductions to 57.82% and 67.05% for cotton and polyester, respectively. Washing cycles also showed a decrease in hydrophobicity after four cycles, indicating a need for enhanced stability and durability. On a positive note, the coating demonstrated only 6.74% and 5.31% of WCA reduction for cotton and polyester, respectively, after 300 abrasion cycles. This excellent abrasion resistance makes the coating suitable for applications requiring hydrophobic and durable textile surfaces. This research could be a huge stepping stone in production of more environmentally friendly hydrophobic coating in various industries including outdoor gear production, automotive, medical textiles and, military and defence.